Analysis of the role of Dirofilaria repens macrophage migration inhibitory factors in host–parasite interactions - Karabowicz Justyna; Długosz Ewa; Bąska Piotr; Pękacz Mateusz; Wysmołek Magdalena Elżbieta; Klockiewicz Maciej; Wiśniewski Marcin (Journal of Veterinary Research)
Dirofilaria repens is a zoonotic parasitic filarial nematode that infects carnivores and occasionally humans. Knowledge of the host–parasite molecular interactions enabling the parasite’s avoidance of the host immune response in subcutaneous dirofilariasis remains limited. Parasitic orthologues of host macrophage migration inhibitory factor (MIF) are molecules potentially involved in this process.